Composition, antibacterial and anti-oxidant potentials of the essential oil of Hedychium matthewii (Bangladesh Journal of Pharmacology, 2017)
Essential oils are known for their medicinal value since time immemorial and continue to be of vital importance until the present day. The present study describes the composition, antibacterial and anti-oxidant potential of rhizome oil of Hedychium matthewii. Thirty-five constituents of the oil were identified to account for 82.7%, of which 85.7% was monoterpes and the rest were sesquiterpnes. Most of the major constituents were alcohols and linalool was the prominent one (45.7%). The antibacterial assay showed the bactericidal effect of the essential oil and the most susceptible organism was Streptococcus hemolyticus with a zone of inhibition of 33.8 ± 1.7 mm. The reducing power and nitric oxide scavenging activity of the essential oil was far exceeding the reference compound ascorbic acid and it could be the sign of the potential anti-oxidant power of the oil isolated. The present study also revealed the prospective of H. matthewii as a new natural source of linalool, which has medicinal and various industrial applications.